2020
DOI: 10.1002/adhm.202001373
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Antiinflammatory Material Design

Abstract: Implants and prostheses are widely used to replace damaged tissues or to treat various diseases. However, besides the risk of bacterial or fungal infection, an inflammatory response usually occurs. Here, recent progress in the field of anti‐inflammatory biomaterials is described. Different materials and approaches are used to decrease the inflammatory response, including hydrogels, nanoparticles, implant surface coating by polymers, and a variety of systems for anti‐inflammatory drug delivery. Complex multifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 174 publications
(135 reference statements)
0
27
0
Order By: Relevance
“…In addition, several studies have shown that modifications in polymer surface nanotopography (i.e., surface roughness) can lead to increased chondrocyte density and protein production due to enhanced protein binding on micro-and nano-rough surfaces (Storey and Webster, 2014). Advances in anti-inflammatory polymers or polymeric coatings may be of great use to this field as well-this is an active area of research for surgical implants in general, reviewed recently by both Sánchez-Bodón et al and Lebaudy et al (Bridges and García, 2008;Al-Khoury et al, 2019;Lebaudy et al, 2021;Sánchez-Bodón et al, 2021). Recent work in this field has also evolved to incorporate decellularized extracellular matrix (dECM) from cartilage and IVD into 3D-printable bioinks to aid in guiding cell proliferation, attachment, and differentiation (Vernengo et al, 2020).…”
Section: Future Outlookmentioning
confidence: 99%
“…In addition, several studies have shown that modifications in polymer surface nanotopography (i.e., surface roughness) can lead to increased chondrocyte density and protein production due to enhanced protein binding on micro-and nano-rough surfaces (Storey and Webster, 2014). Advances in anti-inflammatory polymers or polymeric coatings may be of great use to this field as well-this is an active area of research for surgical implants in general, reviewed recently by both Sánchez-Bodón et al and Lebaudy et al (Bridges and García, 2008;Al-Khoury et al, 2019;Lebaudy et al, 2021;Sánchez-Bodón et al, 2021). Recent work in this field has also evolved to incorporate decellularized extracellular matrix (dECM) from cartilage and IVD into 3D-printable bioinks to aid in guiding cell proliferation, attachment, and differentiation (Vernengo et al, 2020).…”
Section: Future Outlookmentioning
confidence: 99%
“…[ 1a ] Materials trying to overcome this problem, and more particularly inducing macrophage differentiation into M2 (proresolving) instead of M1 (proinflammatory) phenotype are also under development. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterial-based therapy is a useful method to improve bone regeneration; however, its underlying repair mechanism is not yet elucidated [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. About 30 years ago, the French surgeon Alain-Charles Masquelet developed a new technique to repair bone defects called the Masquelet induced membrane [ 41 ].…”
Section: Introductionmentioning
confidence: 99%